Immune dysfunction in MGAT2‐CDG: A clinical report and review of the literature. Issue 1 (12th October 2020) - Poskanzer, Sheri A.; Schultz, Matthew J.; Turgeon, Coleman T.; Vidal‐Folch, Noemi; Liedtke, Kris; Oglesbee, Devin; Gavrilov, Dimitar K.; Tortorelli, Silvia; Matern, Dietrich; Rinaldo, Piero; Bennett, James T.; Thies, Jenny M.; et al.
Abstract: Glycosylation is a critical post/peri‐translational modification required for the appropriate development and function of the immune system. As an example, abnormalities in glycosylation can cause antibody deficiency and reduced lymphocyte signaling, although the phenotype can be complex given the diverse roles of glycosylation. Human MGAT2 encodes N‐acetylglucosaminyltransferase II, which is a critical enzyme in the processing of oligomannose to complex N‐glycans. Complex N‐glycans are essential for immune system functionality, but only one individual with MGAT2‐CDG has been described to have an abnormal immunologic evaluation. MGAT2‐CDG (CDG‐IIa) is a congenital disorder of glycosylation (CDG) associated with profound global developmental disability, hypotonia, early onset epilepsy, and other multisystem manifestations. Here, we report a 4‐year old female with MGAT2‐CDG due to a novel homozygous pathogenic variant in MGAT2, a 4‐base pair deletion, c.1006_1009delGACA. In addition to clinical features previously described in MGAT2‐CDG, she experienced episodic asystole, persistent hypogammaglobulinemia, and defective ex vivo mitogen and antigen proliferative responses, but intact specific vaccine antibody titers. Her infection history has been mild despite the testing abnormalities. We compare this patient to the 15 previously reported patients in the literature, thus expanding both the genotypic and phenotypic spectrum for MGAT2‐CDG.